Self-Centering Steel Frame Systems for Seismic-Resistant Structures - Lihua Zhu; Cheng Zhao (Advances in Civil Engineering)
This paper introduces a review of self-centering steel frame systems for seismic-resistant structures. The components and basic mechanisms of the developing posttensioned connections and self-centering braces are briefly introduced. The structural details and seismic behaviors of the self-centering systems proposed in recent years, including connections, energy dissipating braces, and steel frames, are condensed in categories. The theoretical and experimental results indicated that self-centering action could minimize residual deformation and structural damage. The energy dissipating capability of the self-centering systems is greatly enhanced by the application of energy dissipating device. The shape memory alloys (SMAs) and prepressed springs which exhibited great potential in energy dissipation and recentering capability have been studied increasingly in recent years. Abundant numerical models were propounded to investigate the cyclic response of these self-centering systems. The current research challenges and the critical issues which need further study are discussed at the end of this paper.